Potencial do Pupinus albescens Hook. & Arn. para recuperação de solos arenizados do bioma pampa - Rovedder, Ana Paula Moreira (2007)
As the productive processes move forward on the sandy soils of the Southwest region of Rio Grande do Sul, the arenização has been assuming relevance as factor of soil and regional ecosystem degradation. Contention measures should be established to avoid the progress of the arenização focuses and to recover the areas already damaged. Among these strategies, the revegetation with native species of Bioma Pampa can be seen as alternative ecological and economically viable, at the same time in that it values the local biodiversity. After having established the revegetation, the obtained results should be monitored. In the present study, Lupinus albescens Hook & Arn., specie of native legume of the Southwest region, had its potential as recovering species of degraded soils tested. The potential of biomass production and the macronutrientes accumulation in the biomass of the aerial part was evaluated and tests were done for characterization of the bacterial fixing of nitrogen, symbiotic to the Lupinus albescens. As recommendation for sowing were tested spacings of 17, 34 and 51 cm between rows and 4, 8, 12, 16 and 20 plants for lineal meter. The soil fauna was used as bioindicador to evaluate possible improvements in the soil environment with the use of this specie. Their population characteristics were compared (abundance, richness, diversity and equitability of Shannon index) among revegetation area with Lupinus albescens 3 years ago (T3), revegetation with Lupinus albescens 1 year ago (T1), area of natural occurrence of Lupinus albescens (TN), native grass field (CN) and degraded soil (SA). With the same objective, the content of carbon, macronutrients and aluminum was evaluated in the depths from 0 to 5 and 5 to 10 cm in these same treatments, more native grassfield without grazing 3 years ago (CN3). The results showed efficiency in the production of biomass and macronutrientes accumulation in the aerial part of Lupinus albescens. In relation to the bacterium symbiotic it was observed fast colonization and production of organic acids. It was not possible to establish a combination among spacing between rows and number of plants for more appropriate lineal meter to the cultivation of the Lupinus albescens due to the high genetic variability of the specie. The isolated analysis of the row spacing showed that the spacing of 17 cm among rows was more efficient for production of dry mass and macronutrients accumulation in the vegetable tissue. For seeds production, the spacings of 34 and 51 cm among rows were more efficient. The number and weight of nodules of nitrogen fixing were not influenced by row spacing. In relation to the comparative study with recovery indicators was observed that the soil fauna responds more quickly to the revegetation that the soil chemical characteristics. The treatments with vegetation (T3, T1, TN, CN) presented larger abundance values comparatively to the degraded soil (SA). SÁ presented larger diversity index due to the largest equitability among groups. It was noticed the tendency of dominancy of determined groups. In the treatments with vegetation Hymenoptera and Collembola prevailed. In SA, Hymenoptera and Coleoptera prevailed. In relation to the macronutrients contents and carbon in the soil, it was also observed larger values in the vegetated treatments when in comparison with the degraded soil. The treatment T1 presented residual effect of the nitrogen application. The treatment TN stood out in potassium content, calcium and magnesium. The treatment SA presented the smallest averages for macronutrients and soil carbon, showing higher medium for aluminum content. This analysis was efficient to characterize the effect of the vegetable covering and the degradation, demonstrating the difficulty of recovery of this compartment in the sandy soils of the region. The factors textural class, presence or absence of vegetable covering, period of time with vegetable covering and its management kind were the most decisive for the chemical characteristics evaluated. The revegetation with Lupinus albescens as strategy of recovery of sandy soils is viable due to its potential for production of dry mass and nutrient cycling. However, due to the low resilience of the local ecosystem, their results, mainly in relation to increment in carbon and macronutrients of the soil are felt slowly.